Partial anomalous pulmonary venous drainage in patients presenting with suspected pulmonary hypertension: A series of 90 patients from the ASPIRE registry. Issue 10 (6th April 2020) - Lewis, Robert A.; Billings, Catherine G.; Bolger, Aidan; Bowater, Sarah; Charalampopoulos, Athanasios; Clift, Paul; Elliot, Charlie A.; English, Kate; Hamilton, Neil; Hill, Catherine; Hurdman, Judith; Jenkins, Petra J.; et al.
ABSTRACT: Background and objective: There are limited data regarding patients with PAPVD with suspected and diagnosed PH. Methods: Patients with PAPVD presenting to a large PH referral centre during 2007–2017 were identified from the ASPIRE registry. Results: Ninety patients with PAPVD were identified; this was newly diagnosed at our unit in 71 patients (78%), despite 69% of these having previously undergone CT. Sixty‐seven percent had a single right superior and 23% a single left superior anomalous vein. Patients with an SV‐ASD had a significantly larger RV area, pulmonary artery and L‐R shunt and a higher % predicted DLCO (all P < 0.05). Sixty‐five patients were diagnosed with PH (defined as mPAP ≥ 25 mm Hg), which was post‐capillary in 24 (37%). No additional causes of PH were identified in 28 patients; 17 of these (26% of those patients with PH) had a PVR > 3 WU. Seven of these patients had isolated PAPVD, five of whom (8% of those patients with PH) had anomalous drainage of a single pulmonary vein. Conclusion: Undiagnosed PAPVD with or without ASD may be present in patients with suspected PH; cross‐sectional imaging should therefore be specifically assessed whenever this diagnosis is considered. Radiological and physiological markers of L‐R shunt are higher in patients with an associated SV‐ASD. Although many patients with PAPVD and PH may have other potential causes of PH, a proportion of patients diagnosed with PAH have isolated PAPVD in the absence of other causative conditions. Abstract : PAPVD was frequently missed in patients presenting with suspected PH. L‐R shunt was higher in patients with associated ASD. Although patients may have other potential causes of PH, some patients with PAH have isolated PAPVD without other causative conditions. See related Editorial